A Study On Factors Inducing Stress Among Students In Nursing College - Fareed Ammar (GoAcademica Research & Publishing, 2021)
Seventy students in nursing collage from Basrah in Iraq during their first year study year used questionnaires of 22 items that include social, educational and health factors that could induce stress in the students. Statisctial mean score method is used for analysis. The study showed most significant factors that induce student stress are educational and health factors and the mean score values are found to be 1.5 and 1.63 respectively. Financial and work load were the more effective factors that induced stress in nursing students due to low financial support and hard learning subjects.